On the Cauchy Problem for the Equation of Finite-depth Fluids (Journal of Partial Differential Equations, 1992)
Some properties of the singular integral operator G(&#8901) and the solvability of Cauchy problem for the singular integral-differential equations (1.1) and (1.2) of finite-depth fluids are studied.
Keywords: Singular integral differential equation; Joseph equation; Cauchy problem; a priori estimates; Solvability